2020
DOI: 10.1186/s12903-020-1050-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cervical preflaring and root canal preparation on the fracture resistance of endodontically treated teeth

Abstract: Background: Evaluate the fracture resistance of endodontically treated teeth after cervical preflaring and root canal preparation and to assess the volume of the root canal and the amount of remaining root dentin before and after cervical preflaring. Methods: Forty-four mandibular incisors were selected using micro-CT scanning and distributed into 4 groups (n = 11) according to the instrument used for cervical preflaring: control group -no cervical preflaring; Gates Gliddenburs size #2 and #3; WXN -25.07 Navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…[2][3][4][5] It is reported that additional effects from occlusal forces will result in vertical root fractures due to thinning of dentin walls with excessive shaping of the root canal, and microcracks occurring in these root walls. [7][8][9]30 It is stated that the thickness of the root dentin in the furcation area is considerably reduced, especially in the lower primary molars, and these areas should be considered danger zones. 5 It has been reported that this variation is more common and diversified in mesial roots, and angulation is also higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] It is reported that additional effects from occlusal forces will result in vertical root fractures due to thinning of dentin walls with excessive shaping of the root canal, and microcracks occurring in these root walls. [7][8][9]30 It is stated that the thickness of the root dentin in the furcation area is considerably reduced, especially in the lower primary molars, and these areas should be considered danger zones. 5 It has been reported that this variation is more common and diversified in mesial roots, and angulation is also higher.…”
Section: Discussionmentioning
confidence: 99%
“…Besides anatomical vulnerability to weakness, it is also stated that the working principles of the rotary systems and the designs of the files may cause overpreparation or microcracks in the dentin walls. [7][8][9] There is no consensus on whether file designs and movement properties cause dentin defects or complications. Some researchers claim that there is no causal relationship, 10 whereas others claim that the stress created at the root is affected by these variables and that there is a potential relationship between them.…”
mentioning
confidence: 99%
“…In addition, the preparation tends to preserve the original root canals anatomy (Vertucci, 2005). Also, the preflaring is a fundamental step in the treatment, as in addition to removing the most infected dentin portion, it favors the establishment of the WL and the anatomical diameter (Borges et al, 2018;da Silva et al, 2020;Plotino et al, 2020), factors that better adjust the file in the apical region (Barroso, Guerisoli, Capelli, Saquy, & Pécora, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since the cervical third of the root canal is the most contaminated region, efforts are made to minimize this condition. Thus, cervical preflaring favors the determination of working length (WL) and anatomical diameter, and minimizes accidents (Borges, Damião, Pereira, Filho, Miranda-Pedro, Luiz de Oliveira da Rosa, Piva, & Guedes, 2018;da Silva, Duarte, Alcalde, Duarte, Vivan, da Rosa, Só, & do Nascimento, 2020;Plotino, Nagendrababu, Bukiet, Grande, Veettil, De-Deus, & Aly Ahmed, 2020). Despite being the region that generally suffers the most from the instruments, da Silva et al (2020), in a study with mandibular incisors, concluded that preflaring and root canal preparation itself reduced dentinal thickness, however, NiTi instruments were not able to change the fracture resistance of these teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of dental structure caused by endodontic treatment is responsible for a decrease in tooth resistance, which increases susceptibility to fracture [ 1 ]. The longevity of endodontically treated teeth is influenced by several factors, such as, the preservation of remaining dental tissue, effectiveness of restorative procedures and occlusal force [ 2 ].…”
Section: Introductionmentioning
confidence: 99%